Effect of Na+ on hydration degree of alkali activated metakaolin polymer - Zhao Yagebai; Wang Hongguang; He Yao; Yang Lanjie; Wu Hao (Magazine of Civil Engineering, 2022)
In recent years, geopolymeric gel materials have become a hot research issue due to their good mechanical properties, durability and excellent chemical stability. In this paper, Na+-metakaolin soil polymer was prepared by activating metakaolin with a combination of NaOH and sodium silicate. Taking Na's influence on the hydration degree of alkali-activated metakaolin soil polymer as the goal, we selected Na2O equivalent and the modulus of the alkali activator, two most important factors for Na+ content in the system, as the object of our studies. The effect of Na2O equivalent and modulus on the degree of hydration of geopolymers was analyzed by testing the compressive strength of metakaolin land polymers and microscopic SEM, FT-IR and XRD. The results show that the optimal activation environment for metakaolin is 18 % Na2O equivalent and 1.5 modulus. When the Na2O equivalent is less than 18 %, as the Na2O equivalent increases, the degree of hydration of the metakaolin land polymer deepens. When it is greater than 18 %, with the Na2O equivalent, the first stage of the geopolymer hydration reaction is suppressed and the degree of kaolin hydration is partially weakened. When the modulus is less than 1.5, as the modulus increases, the rate of the first stage of geopolymerization is accelerated, and the degree of hydration is deepened. When the modulus is greater than 2.0, as the modulus increases, the geopolymerization hydration reaction is suppressed during the second and third stages, the formation rate of geopolymeric gel is slowed down and the degree of hydration is weakened.